2010
DOI: 10.2967/jnumed.109.072447
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Smoking-Induced Occupancy of β2-Nicotinic Acetylcholine Receptors: Estimation of Nondisplaceable Binding

Abstract: 5-123I-iodo-85380 (123I-5-IA) is used to quantitate high-affinity nicotinic acetylcholine receptors (β2-nAChRs) on human SPECT scans. The primary outcome measure is VT/fP, the ratio at equilibrium between total tissue concentration (free, nonspecifically bound, and specifically bound) and the free plasma concentration. Nondisplaceable uptake (free plus nonspecific) of 123I-5-IA has not been measured in human subjects. Nicotine has high affinity for β2*-nAChRs (nAChRs containing the β2* subunit, for which * rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
6
30
0
Order By: Relevance
“…In addition to the participants described in this paper, 11 smokers completed study procedures, but were excluded from the data analysis because their plasma nicotine levels were unacceptably high (> 0.4 ng/mL) (determined after study participation). This issue of smokers using nicotine/tobacco during the abstinence period of a brain-imaging study has been reported in prior studies by our group and others (Brody et al 2013; Esterlis et al 2010; Staley et al 2006), presumably related to difficulty in having tobacco-dependent smokers remain abstinent for a prolonged period.…”
Section: Methodssupporting
confidence: 74%
“…In addition to the participants described in this paper, 11 smokers completed study procedures, but were excluded from the data analysis because their plasma nicotine levels were unacceptably high (> 0.4 ng/mL) (determined after study participation). This issue of smokers using nicotine/tobacco during the abstinence period of a brain-imaging study has been reported in prior studies by our group and others (Brody et al 2013; Esterlis et al 2010; Staley et al 2006), presumably related to difficulty in having tobacco-dependent smokers remain abstinent for a prolonged period.…”
Section: Methodssupporting
confidence: 74%
“…Comparison subjects were excluded for lifetime exposure to psychiatric medication, except for smoking cessation attempts (and none in the past year). Nicotine dependence was evaluated with the Fagerström Test for Nicotine Dependence (20). Smoking status at screening was verified by a plasma cotinine level > 150 ng/ml, urine cotinine level > 100 ng/ml, and carbon monoxide (CO) level > 11 ppm at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…β 2 * -nAChRs have been previously quantified with high affinity radioligand [ 123 I]-5 -iodo-3-[2(S)-2-azetidinylmethoxy]pyridine ([ 123 I]5-IA) (17) and SPECT (18). in a range of clinical samples including individuals with nicotine addiction (19, 20), alcohol use disorders (21), major depressive disorder (22), bipolar disorder (23), and schizophrenia (16)) [ 123 I]5-IA has slow dissociation from the receptor–ligand complex, a good specific to nonspecific binding ratio, and high selectivity for β 2 * -nAChRs (18, 24). We hypothesized that although there would be overall lower β 2 * -nAChR availability in individuals with vs. without schizophrenia, we would observe higher β 2 * -nAChR availability in smokers vs. nonsmokers with schizophrenia in the cortex, hippocampus, and striatum based on previous postmortem findings (15).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, previous PET and SPECT experiments found that smoking to satiety resulted in a4b2* nAChR occupancies of 70% to 100%. 36,38 These data suggest the possibility of incorporating a complete displacement dose of nicotine to regionally determine V ND in MI studies.…”
Section: Analysis With Compartment Modelingmentioning
confidence: 88%